A UK pilot study: The specificity of the Word Memory Test effort sub‐tests in acute minimal to mild head injury. Issue 2 (16th May 2013) - Hall, Vicki L.; Worthington, Andrew; Venables, Katie
<x xml:space="preserve">Abstract</x> The specificity of the Word Memory Test (WMT) effort indices was examined in 48 individuals with minimal to mild head injury (MHI) in the acute stages post‐injury. None of the individuals was involved in litigation or disability claims. At the established cut‐offs, the WMT had an unacceptable false‐positive rate (18%). T test analysis was also carried out for WMT passers and failures on a battery of neuropsychometric measures and across a range of demographic variables. The WMT was performed at a significantly lower level on the Wechsler Memory Scale – III word list sub‐tests and verbal fluency tests (p < .05). This suggests that WMT failure may be indicative of a specific deficit in verbal processing in the acute phase of MHI.